The Attitude Measurement towards Coaching Profession and the Level of Ambition for the Varsity Players in Kurdistan Region Tournament - Odeesho Asee, Udeed; Sa’dun Omer, Falah (Journal of Duhok University, 2019)
The aim of the study was to identify the nature of the attitude of the players in the Kurdistan varsity League towards sport coaching profession and also aimed to know the level of athletic ambition for both games Basket Ball and Volley ball as well as the knowledge of differences of attitude and the ambition between the players according to the game and according to the clubs, the researcher used the method of descriptive in his study for it is the best and common method for such studies for it analyze and evaluate and diagnosis the phenomenon by using umbers and data. The Society and the study Sample includes Basketball players and volley ball players the numbers of clubs for Basket was ( 8 ) teams which is ( 96 ) players from all cities and provinces of